A FIXED POINT APPROACH TO THE FUZZY STABILITY OF A QUADRATIC-QUARTIC FUNCTIONAL EQUATION - Choonkil Park; Jung Rye Lee; Dong Yun Shin (Tạp chí Khoa học Đại học Đà Lạt)
Using fixed point method, we prove the Hyers-Ulam stability of the following quadratic-quartic functional equation f(x + 2y) + f(x - 2y) = 4f(x + y) + 4f(x - y) - 6f(x) + 2f(2y) - 8f(y) in fuzzy Banach spaces